Hoax and Fake News During Covid-19: Is the Law Effective in Overcoming It? - Khoirum Lutfiyah (Universitas Negeri Semarang, 2020)
The world is currently experiencing a pandemic due to a new virus. This virus, called Corona, attacks the respiratory system in humans. Symptoms experienced if infected with the Corona virus (COVID-19) in the form of flu, dry cough, high fever, and shortness of breath. A bad result of contracting the corona virus is that it can cause death. Corona virus can affect anyone, especially in people who have weak body immunity. In matters of emergency like this, it turns out that it is still a person who exploits it by spreading false or fake news. The elements, making lies and then spread through social media, such as Facebook, Instagram, Twitter and the like. They spread hoaxes with a fad. Resulting in people becoming panicked and worried about the corona virus. Hoax news is news that is not necessarily true and its source is not necessarily valid. In this event, the role of government is needed for the community. Persons who spread false news will be charged with Law Number 11 Year 2008 regarding Information and Electronic Transactions as Sanctions imposed on them.